Sol–gel spin coating assisted room temperature operated nanostructured ZnO ethanol sensor with behavior transformation - Beniwal A.; Sahu P.K.; Sharma S. (My University, 2025)
In this paper, zinc oxide (ZnO) thin film sensor has been fabricated using different sol–gel spin coating route to detect very low concentration (2 ppm) of ethanol vapors at room temperature (RT). The sensor shows appreciable response ~60% for 100 ppm of ethanol (C2H5OH) vapors at RT under humidity level ~55% RH. Various sensing parameters viz. % response, selectivity, stability, response/recovery time, repeatability, and reproducibility have been studied successfully. Structural and morphological properties have been studied via X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRD reveals the wurtzite structure of polycrystalline ZnO thin film. AFM, SEM, and TEM results confirm the wavy structure of well-shaped and slackly distributed ZnO nanograins with average particle size in range ~15–25 nm. The analyte sensing properties at room temperature can be ascribed to higher specific surface area due to nanograins formation. The significant effect of operating temperature on sensor’s performance is also analysed in order to obtain the optimum temperature (Topt) of the sensor device. Response reaches to 321.7% for 100 ppm of ethanol vapors at Topt (175 °C). The transformation in the behavior of sensing layer is observed which is described on the basis of experimental studies. [Figure not available: see fulltext.]. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.